Platelet yield and yield consistency for six single-spin methods of platelet rich plasma preparation. (3rd July 2020) - Harrison, Theodore E.; Bowler, Jannice; Levins, Todd N.; Cheng, An-Lin; Reeves, K. Dean
Abstract: Single-spin methods of preparation of platelet-rich plasma are used widely in private practice, yet they have not been extensively studied and compared. The use of platelet-rich plasma (PRP) by the private practitioner can be facilitated by efficient and predictable PRP preparation. The primary purpose of this study was to study common methods of single-spin PRP preparation to determine their efficiency and variability. Six single-spin methods of PRP production from whole blood were analyzed. The primary measures were mean yield and standard deviation as the quotient of total platelet count in PRP produced divided by total platelet count in whole blood utilized. Each sample was analyzed in triplicate and the results were averaged. Secondary measures included red blood cell count (RBC) and white blood cell count (WBC), concentration ratio, and variable cost per million platelets produced. Sixty-four volunteers provided samples from 30 June 2017 to 30 September 2018. Seventeen to twenty six samples were utilized to assess each method. Yields for the six preparation methods (PMs) varied from 53(±18)% to 72(±13)%. Differences were observed for WBC count (1.8 to 14), Hematocrit (0.8 to 32), platelet concentration (568 to 1062), and variable cost per billion platelets produced ($1.55 to $44.31). All six methods evaluated provided a platelet yield of more than 50%, although two methods were less efficient than the others. Two methods were able to produce leukocyte-poor PRP. Variability was moderate across all methods, suggesting that estimation of platelet yield should be feasible from a baseline platelet count for all methods.